2021
DOI: 10.1021/acsomega.0c06016
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of Octacalcium Phosphate Behavior in Different Model Solutions

Abstract: Octacalcium phosphate (OCP), a new-generation bone substitute material, is a considered precursor of the biological bone apatite. The two-layered structure of OCP contains the apatitic and hydrated layers and is intensively involved in ion-exchange surface reactions, which results in OCP hydrolysis to hydroxyapatite and adsorption of ions or molecular groups presented in the environment. During various in vitro procedures, such as biomaterial solubility, additive release studies, or the functionalization techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
(78 reference statements)
1
4
0
Order By: Relevance
“…The empirically fitted reaction orders obtained for the crystallization of struvite and hydroxyapatite were 0.6 and 0.13, respectively (see Table ). The fractional order of reaction indicated that both reactions were nonelementary and suggested the involvement of a series of multiple steps rather than one single step, in agreement with the three steps reported earlier for struvite and the five steps reported for hydroxyapatite crystallization in previous studies. …”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The empirically fitted reaction orders obtained for the crystallization of struvite and hydroxyapatite were 0.6 and 0.13, respectively (see Table ). The fractional order of reaction indicated that both reactions were nonelementary and suggested the involvement of a series of multiple steps rather than one single step, in agreement with the three steps reported earlier for struvite and the five steps reported for hydroxyapatite crystallization in previous studies. …”
Section: Resultssupporting
confidence: 88%
“…Hydroxyapatite crystallization starts with the formation of unstable amorphous calcium phosphate, followed by the hydration, dissolution, and recrystallization steps to form octacalcium phosphate . The formed octacalcium phosphate may experience rapid hydrolysis to yield thermodynamically stable hydroxyapatite crystal nuclei via a topotactic reaction, followed by the crystal growth. ,, The stoichiometry of hydroxyapatite formation is shown in Scheme B.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the use of OCP as a bone substitute material is of interest from the point of view of osteogenesis in intramembranous ossification [ 36 , 37 ]; however, its clinical utility is still unclear and there is a lack of evidence compared to β-TCP or calcium sulfate, which are widely used in orthopedics. Regarding the phase composition, OCP has a two-layered structure of hydrate and apatite layers, and the apatite layers are involved in ion–exchange reactions at the phase boundary between the material and given environment [ 38 ]. Moreover, OCP has been proposed as a precursor of biological apatite in bones and OCP was reabsorbed by osteoclasts in addition to dissolution by pH in the body [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two-layered structure of OCP contains the apatitic and hydrated layers and is intensively involved in ion-exchange surface reactions, which results in OCP hydrolysis to hydroxyapatite (HA) and adsorption of ions or molecular groups presented in the environment as motion species ((HPO 4 ) 2− , Ca 2+ , OH 1− ). The composition of the solution and environmental structure (collagen matrix) affects the degree and rate of OCP hydrolysis, its surface reactivity and further in vitro and in vivo properties [ 13 ].…”
Section: Introductionmentioning
confidence: 99%